JustFoodForDogs : the world's first dog kitchen - Rapier, Stephen M.; Shanahan, Doreen E. ([London] : SAGE, 2016)
Founder Shawn Buckley and partner Rudy Poe opened JustFoodForDogs in January 2011 in a 1300 square foot retail kitchen in Newport Beach, California, where they produced and sold human quality healthy food for dogs. In the spring of 2013, confident in their concept, the two partners decided to open a second location in West Hollywood, California. The site for their new location was 50 miles away from their first location. With limited knowledge of the local market in the new location, the founders questioned if the positioning, messaging strategy and brand elements used in their first location would resonate as well in the new market.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Marketing -- Management -- Case studies